PHENOTYPIC CHARACTERIZATION OF TWO INDIGENOUS CHICKEN ECOTYPES OF PAKISTAN - A. Iqbal; A. Ali; K. Javed; M. Akram; M. Usman; S. Mehmood; J. Hussain; F. Hussnain (Journal of Animal and Plant Sciences, 2015)
Aseel and Naked-neck chickens from various regions of Pakistan were studied (n=200; 100 (40♂, 60♀) in each) for phenotypic characterization based on head appearance; comb type; wattles size; colors and patterns of feathers on neck, breast, wing-bow, wing-bar, wing-bay, saddle and tail; shank color; spurs prevalence, and number of toes. Feather colors and patterns on the neck, breast, wing-bow, wing-bar, wing-bay, saddle and tail (P<0.000) and shank color (P<0.042) differed significantly between ecotypes. Both ecotypes had plain head. All Aseels had pea-comb, no wattles, fully feathered necks, predominantly dark-brown neck feathers (35%), pale-brown breast (32%), wing-bow (33%), wing-bar (35%), wing-bay (35%), saddle (32%) and black/gray tail feathers (44%). Majority (33%) had yellow shanks. Naked-necks possessed single-comb, predominantly medium sized wattles (53%), white/off-white neck (35%) and breast feathers (43%), dark-brown wing-bow feathers (21%), off-white wing-bar (26%) and pale-brown/orange-brown wing-bay (28%), black saddle (22%) and tail feathers (57%), yellow shanks (36%). Both ecotypes had four toes and normal spurs. Among Aseels, some hens also had spurs which is a unique feature not reported in previous studies to the knowledge of the authors. Predominantly both ecotypes had plain feathers but patterns were also present.
Keywords: Phenotype; Aseel; Pakistan; Conservation; Naked-neck